The Influence of Principal’s Leadership and Work Discipline on Teacher’s Performance (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to find out and describe the influence of the principal’s leadership on the performance of teachers, work discipline on the performance of teachers, and the influence of the principal’s leadership and teacher work discipline together on the performance of teachers at SD Negeri Gugus 1, Teluk Gelam District, Ogan Komering Ilir Regency. This research was carried out at SD Negeri Gugus 1, Teluk Gelam District, Ogan Komering Ilir Regency with a research sample of 70 teachers. Data collection techniques were carried out through observation, documentation studies, and distribution questionnaires. The validity test uses construct validity, while the reliability test uses Cronbach’s Alpha. The results of this research show that there is a partially significant influence between the principal’s leadership and work discipline on teacher’s performance, and there is a significant simultaneous influence between leadership and work discipline on teacher’s performance at SD Negeri Gugus 1 Teluk Gelam District, Ogan Komering Ilir Regency. It means all schools should focus on principal’s leadership and work discipline of teacher to get excellent teacher’s performance.